Bedrock Vadose Zone Storage Dynamics Under Extreme Drought: Consequences for Plant Water Availability, Recharge, and Runoff. Issue 4 (18th April 2022) - Hahm, W. J.; Dralle, D. N.; Sanders, M.; Bryk, A. B.; Fauria, K. E.; Huang, M. H.; Hudson‐Rasmussen, B.; Nelson, M. D.; Pedrazas, M. A.; Schmidt, L.; Whiting, J.; Dietrich, W. E.; et al.
Abstract: Bedrock vadose zone water storage (i.e., rock moisture) dynamics are rarely observed but potentially key to understanding drought responses. Exploiting a borehole network at a Mediterranean blue oak savanna site—Rancho Venada—we document how water storage capacity in deeply weathered bedrock profiles regulates woody plant water availability and groundwater recharge. The site is in the Northern California Coast Range within steeply dipping turbidites. In a wet year (water year 2019; 647 mm of precipitation), rock moisture was quickly replenished to a characteristic storage capacity, recharging groundwater that emerged at springs to generate streamflow. In the subsequent rainless summer growing season, rock moisture was depleted by about 93 mm. In two drought years that followed (212 and 121 mm of precipitation) the total amount of rock moisture gained each winter was about 54 and 20 mm, respectively, and declines were documented exceeding these amounts, resulting in progressively lower rock moisture content. Oaks, which are rooted into bedrock, demonstrated signs of water stress in drought, including reduced transpiration rates and extremely low water potentials. In the 2020–2021 drought, precipitation did not exceed storage capacity, resulting in variable belowground water storage, increased plant water stress, and no recharge or runoff. Rock moisture deficits (rather than soil moisture deficits) explain these responses. Plain Language Summary: When rainfall is lower than normal, water stored belowground can sustain forests and drain to streams. Does the presence of deep, dynamic water storage in bedrock below soil provide enhanced drought resilience? We used a network of deep boreholes drilled into hillslopes to study how the weathered bedrock unsaturated zone acts as a water source for woody vegetation and mediates groundwater recharge. At our winter‐wet, summer‐dry oak savanna field site in the Northern California Coast Range, dry season reductions in rock moisture were driven by woody plant water use. However, the water storage capacity of the subsurface exceeded net precipitation inputs in dry winters. Thus, deep water storage was not replenished during an extreme drought to the same degree as in wetter years, resulting in decreased groundwater recharge and streamflow, and lower water availability for trees—even those deeply rooted in the bedrock. Trees using bedrock‐water exhibited dieback in the second year of the hot, dry 2020–2021 drought. These findings motivate expanded study of how moisture storage properties of deep bedrock influence the susceptibility of vegetation to drought over multiple years. Key Points: Multi‐year field study reveals role of deep bedrock moisture within hillslopes Large deep storage capacity relative to precipitation in dry years drives variable interannual storage Drought reduced rock moisture replenishment, groundwater recharge, streamflow, and blue oak water potential, transpiration and leaf area